Synthesis and characterization of copper-manganese, oxide octahedral molecular sieves, [3X3], [2x2] OMS, and rubidium-oms, with a [2x4] tunnel - Tolentino, Elaine M. Nicolas (Animo Repository, 1998)
A series of [3x3] manganese oxide octahedral molecular sieves (OMS-1) with copper incorporated in their structures were prepared by hydrothermal synthesis at 160 degrees Centigrade for 8 h. Another series of IMS with [2x2] tunnel structure containing copper was prepared by reflux method. The effects of Cu uptake on the structure, thermal stability, conductivity, electrochemical properties and catalytic activity were investigated. XRD, XPS studies, average oxidation state determination, ICP analyses, EPR, TGA and DSC measurements suggest that Cu2+ substitution in the framework of OMS-1 is possible at high concentration of the cation species in the interlayer sites of OL-1 in the course of its transformation to the tunnel material under hydrothermal conditions. Cyclic voltammetric studies of Cu-OMS-modified indium tin oxide electrodes suggest that the Cu2+ ions in the tunnels are mobile and electroactive. Catalytic evaluation of Cu-containing OMS materials shows a 16 percent and 50 percent conversion for the oxidative dehydrogenation of ethylbenzene to styrene at 300 degrees Centigrade, 1 atm using Cu-OMS-1 C with 13.67 percent Cu.Bulk synthesis of a [2x4] tunnel material using KMnO4,Mn2+, and RbOH by hydrothermal synthesis at 210 degrees Centigrade yielded a thermally stable material at 850 degrees Centigrade in oxygeb stream. Scanning electron micrographs of the rubidium manganese oxide revealed needle-like structures typical of a tunnel material.